PENGARUH TPP DAN MOTIVASI TERHADAP KINERJA APARATUR SIPIL NEGARA PADA SEKRETARIAT DAERAH KABUPATEN SUMBAWA DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING - Hasbulloh Hasbulloh; Achmad Fauzi; Lalu Edy Herman Mulyono (Master of Management, Mataram University, 2022)
This study examines the effect of additional employee income and work motivation on the performance of civil servants at the Regional Secretariat of Sumbawa Regency with motivation as an intervening variable. The population in this study were employees at the Sumbawa Regional Secretariat, with a sample of 131 respondents in this study. Sampling technique with probability sampling method data analysis using PLS-SEM. The results of this study indicate that the Additional Employee Income (TPP) has a positive and significant effect on performance at the Regional Secretariat of Sumbawa Regency, TPP has a positive and significant effect on employee motivation at the Regional Secretariat of Sumbawa Regency and Motivation has a significant positive effect on employee work motivation at the Sumbawa Regency Secretariat.